The Effect of Resilience on Burnout in Mining Employees at Pt. Berkah Daya Mandiri - Hairunnisa U. Hadjarati; Fendi Ntobuo; Lenny Syamsuddin; Fahri Kamuli (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to determine the effect of resilience to burnout in mining employees at PT Berkah Daya Mandiri. This study uses a quantitative approach by involving 40 employees as respondents through a total sampling technique. Data collection was carried out using a questionnaire consisting of The Connor Davidson Resilience Scale and The Oldenburg Burnout Inventory resilience measurement tool. Data analysis was carried out using simple linear regression to test the research hypothesis. The results of the analysis showed a t-value of 2.769 with a significance value of 0.009 which indicates a positive and significant influence between resilience to burnout in mining employees at PT Berkah Daya Mandiri. The determination coefficient value of 0.168 showed that resilience contributed 16.8 percent to burnout, while the other 83.2 percent was influenced by other variables not studied in this study. In addition, the majority of employees showed a level of resilience and burnout in the medium category of 75 percent each. These findings indicate that even though employees have a fairly good adaptability, high work demands and expectations still have the potential to increase burnout rates.